2006
DOI: 10.1603/0022-0493-99.5.1651
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Various Combinations of Colors and Shapes to Females and Males of <I>Bactrocera minax</I> (Diptera: Tephritidae) in a Commercial Mandarin Grove in Bhutan

Abstract: Bactrocera minax (Enderlein) (Diptera: Tephritidae) is a major pest of citrus fruit in the region from Nepal through to southwestern China. In tests on wild adult populations of B. minax in a mandarin, Citrus reticulata Blanco, orchard in western Bhutan, both males and females were more attracted to 50-mm-diameter spheres than to 50-mm discs of the same color. Furthermore, they were more attracted to spheres colored with orange or green-yellow mixtures than to similar spheres colored red, yellow, green, blue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Bactrocera minax (Enderlein) is an international pest that is often the target of quarantine. Adults lay eggs in the fruit, the result of which can inflict significant economic losses on the citrus industry (Dorji et al, 2006;Drew et al, 2006). The larvae feed on the fruits, causing the fruit to fall off before maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Bactrocera minax (Enderlein) is an international pest that is often the target of quarantine. Adults lay eggs in the fruit, the result of which can inflict significant economic losses on the citrus industry (Dorji et al, 2006;Drew et al, 2006). The larvae feed on the fruits, causing the fruit to fall off before maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Bactrocera minax is an oligophagous and univoltine species that damages citrus fruit, mainly in southern/central China, and many Southeast Asian countries (Wang and Luo, 1995; Drew et al, 2006). Adult flies live by feeding on substances such as honeydew and reach sexual maturity approximately 3 weeks after emerging.…”
Section: Introductionmentioning
confidence: 99%
“…On testing of 15, 22, 35 mm size of fruit mimic balls with non-drying glue during oviposition in Bhutan, most flies were attracted to a green ball of size 22 and 35 mm than 15mm (Schoubroeck, 1999). Another experiment showed that the orange or greenyellow mixtures colored spheres were more efficient than similar-sized red, yellow, green, blue, black, or white spheres of 50mm (Drew et al, 2006). However, this technique seems impractical and less standard for villages (Schoubroeck, 1999).…”
Section: Fruit Mimic Ballsmentioning
confidence: 99%